Analisis Faktor-Faktor yang Berpengaruh terhadap Keputusan Pembelian di E-Commerce Tokopedia - Mohamad Rafki Nazar; Afiva Karina; Kania Khotimah; Shafa Nurul Arafah; Dina Muharani Anggorowati (Departement of Mathematics Education, 2023)
The purpose of this study was to analyze the level of trust, security, and service quality in transactions on purchasing decisions for the Tokopedia application. Descriptive research is the method we use. Using a Likert scale, a survey method was used for sampling. We use multiple linear regression to test this hypothesis. The findings show that the variables of security, trust, and service quality have a significant effect on Tokopedia purchasing decisions, while the variables of reliability and security also have a significant effect.